Leachate Treatment Using Sub-Surface Flow Constructed Wetland by Hippochaetes lymenalis - Ratnawati, Rhenny; Permata Sari, Dinda; Mukhtar, Nushron Ali (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2024)
Leachate, which comes from waste landfills, contains high levels of organic and inorganic matter. Constructed Wetland technology is a suitable alternative for leachate treatment. This technology is easy to apply, relatively cost-effective, and can achieve optimal reduction results for treating and controlling leachate, thereby reducing its environmental impact. The objective of this study was to treat the BOD concentration and COD in leachate using a Constructed Wetland. Data collection was performed by conducting leachate experiments for Constructed Wetland treatment using Hippochaetes lymenalis plants based on variations in residence time and media height. There was a control group (R1) without any media or plants. The variation combination included R2 (containing 10 cm gravel and 10 cm fertile soil) and R3 (containing 5 cm gravel and 15 cm fertile soil). Residence times were set at 0, 7, 14, and 21 d. This research showed that the reactor with growth media consisting of 10 cm gravel and 10 cm fertile soil had 55% and 85% BOD and COD removal efficiencies, with final BOD concentrations and COD values of 273 mg/L and 1,321, respectively. The reactor with growth media consisting of 5 cm gravel and 10 cm fertile soil had 74% and 95% BOD and COD removal efficiency, with the final BOD concentration and COD at 159 mg/L and 432, respectively.